Wetting Heterogeneities in Porous Media Control Flow Dissipation - Schröter, Matthias; Murison, Julie; Semin, Benoît; Baret, Jean-Christophe; Herminghaus, Stephan; Brinkmann, Martin (Physical Review Applied, 2014)
Pressure-controlled displacement of an oil-water interface is studied in dense packings of functionalized glass beads with well-defined spatial wettability correlations. An enhanced dissipation is observed if the typical extension xi of the same-type wetting domains is smaller than the average bead diameter d. Three-dimensional imaging using x-ray microtomography shows that the frequencies n(s) of residual droplet volumes s for different xi collapse onto the same curve. This indicates that the additional dissipation for small xi is due to contact line pinning rather than an increase of capillary break-up and coalescence events.